Higher Order Temporal Rules - Cotofrei, Paul; Stoffel, Kilian (Berlin: Springer-Verlag Berlin, 2003)
The theoretical framework we proposed, based on first-order temporal logic, permits to define the main notions used in temporal data mining (event, temporal rule) in a formal way. The concept of consistent linear time structure allows us to introduce the notions of general interpretation and of confidence. These notions open the possibility to use statistical approaches in the design of algorithms for inferring higher order temporal rules, denoted temporal meta-rules.